THE NAME OF FREEDOM AND THE FUTURE - Baibulsinova, A.; Zhalekenova, G. (Journal of history, 2018)
The article contains historical facts about the life and activity of the Kazakh people in the early twentieth century, about the national liberation political movements and the activity of the Alashorda government’s personalitydoctor Esengali Kasabolatov. Documentary information about his contribution to the development of Kazakh medicine in the Soviet era was given, however, he has been recognized of an innocent victim of politics. As well as socio-political life in the early twentieth century, the activities of the Alashord government, the first and the second General Congress in Orenburg and the current problems of statehood, the creation of the Ak Jol party, the activities of medical workers in the Soviet Union, state accusations of public and political figures, the descendants of E. Kasabolatov, the work and works of the figure.